Food justice in public-catering places: mapping social-ecological inequalities in the urban food systems - Hoinle, Birgit; Klosterkamp, Sarah (Frontiers in Sustainable Food Systems, 2023)
Departing from reflections and observations raised by Food Policy Councils (FPCs) within North America specifically, this article explores the complex material, discursive, and governance aspects of food provision on the urban-regional scale by highlighting recent accounts of public food provision within state-funded public-catering places in Germany. Based on a fieldwork in Southern Germany, and grounded in a methodological approach guided by participatory action research (PAR), participatory observation, feminist GIS, and 17 interviews with different actors within the regional food systems involved we would like to form the basis for pushing these new approaches further toward more food democracy and food justice as we are elevating the key factors and rewards, but also the downsides and challenges of food provision in public catering places regarding social-ecological inequalities. In doing so, the global intimacies of the urban food system on the local scale, their different modes of inclusions and exclusions, and their intersections of inequalities are unpacked by also shifting the focus to the economic and political entanglements at stake within the global sphere of food provision. By amplifying how producers, meal providers, and consumers within the urban food systems perceive (and perhaps contradict) issues of food justice and by coalescing their perspectives about local food system transformations and desires toward food justice and sustainability, not only the challenges at place but also the promises of hope within public-catering places are illustrated.